Long-term Outcomes of Pediatric Tracheostomy Home Care in a Limited Resource Setting of Professional Home Nurse. Issue 4 (November 2022) - Phuaksaman, Chutima; Niyomkarn, Watit; Somboon, Prapasri; Boonjindasup, Wicharn; Hantragool, Sumalee; Sritippayawan, Suchada
Long-term outcomes of pediatric patients with a tracheostomy in developing countries where professional home nurse is not accessible has rarely been reported. We, therefore, investigated the prevalence and associating factors of long-term outcomes in these children. Retrospective chart review was conducted in 85 tracheostomized children who were discharged to home during January 2012 to December 2020. Tracheostomy home care was provided by caregivers who completed the tracheostomy home care program. Prevalence of unplanned readmission with acute respiratory problems within 30 days after the first hospital discharge was 17.6%. Lower respiratory tract infection (LRTI) after hospital discharge was found in 72.9% (median frequency of 1.0 episode/case/year). Among 80 children who had surveillance airway endoscopy, 46.3% demonstrated late tracheostomy-related airway complications. Independent factor associated with late tracheostomy-related airway complications was a follow-up period longer than 1 year. Decannulation success was found in 21.2%. Most of them had tracheostomy for their upper airway anomalies. The mortality rate was 7%. Most of them died from their underlying diseases. In conclusion, pediatric tracheostomy home care undertaken by caregivers is feasible in developing countries where home nurse is not available. The prevalence of unplanned readmission with acute respiratory problems within 30 days after hospital discharge and late tracheostomy-related airway complications were comparable with those reported in developed countries. However, we still had a high prevalence of post-tracheostomy LRTI which was a challenging problem that needed to be investigated and resolved.